Wellbeing and Devolution Reframing the Role of Government in Scotland, Wales and Northern Ireland - Wallace, Jennifer (Wellbeing in Politics and Policy, 2019)
It has been over twenty years since the people of Scotland, Wales and Northern Ireland voted for devolution. Over that time, the devolved legislatures have established themselves and matured their approach to governance. At different times and for different reasons, each has put wellbeing at the heart of their approach - codifying their values and goals within wellbeing frameworks. This open access book explores, for the first time, why each set their goal as improving wellbeing and how they balance the core elements of societal wellbeing (economic, social and environmental outcomes). Do the frameworks represent a genuine attempt to think differently about how devolved government can plan and organise public services? And if so, what early indications are there of the impact is this having on people's lives?